Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian pada Kedai Kopi Melati Ciputat - Darmawan, Muhamad Fikri; Pasaribu, Veta Lidya Delimah (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to determine the influence of promotion and product quality on the purchase decision of Kedai Kopi Melati products. The method used is a quantitative descriptive method with an associative approach. The sampling technique used is Probability Sampling, a sampling method using the Lemeshow formula. Data analysis uses regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are Product Quality (X1) and Promotion (X2) have a positive and significant effect on Purchasing Decisions (Y) with a regression equation Y = 9.678 + 0.113X1 + 0.696X2. The coefficient of determination simultaneously affects 61%. The hypothesis test partially obtained a promotion rate of tcount > ttable or (2.354 > 1.986). Then H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between the independent variable, namely Product Quality (X1) and Purchasing Decision (Y). Product Quality numbers of tcount > ttable or (12,174 > 1,986). Then H0 is rejected and H2 is accepted. This means that there is an influence between the independent variable, namely Promotion (X2) and Purchase Decision (Y). Test the hypothesis obtained the value of Fcalculate > ttable or (77.571 > 2.700) Thus H0 is rejected and H3 is accepted, meaning that the Quality of Promotion (X1) and Promotion (X2) together have a positive effect on Purchase Decision (Y). Keywords: Product Quality, Promotion, Purchase Decision.